2012
DOI: 10.2478/v10118-012-0014-0
|View full text |Cite
|
Sign up to set email alerts
|

Grain-size characteristics of deposits derived from different glacigenic environments of the Schirmacher Oasis, East Antarctica

Abstract: Sediment samples have been collected from the Schirmacher Oasis and adjoining area in East Antarctica; these areas consist of polar ice, ice-free area, lakes and the coastal shelf area. The 37 samples have been analysed for their grain-size parameters and statistical relationships. The oasis is characterised by ongoing glacial processes, including deposition and erosion of the sediments by ice, meltwater and winds, thus influencing the sediments in various ways. Basic statistical grain-size parameters like gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
(15 reference statements)
0
16
0
Order By: Relevance
“…Medium sand is the dominant grain size fraction. The sediment sorting is generally low, however locally increases due to fluvial activity (Srivastava et al, 2012). Contribution of the eolian processes is also probable as far as windblown material was detected within the supraglacial sediments near Schirmacher Oasis (Asthana and Chaturvedi, 1998).…”
Section: Study Areamentioning
confidence: 99%
“…Medium sand is the dominant grain size fraction. The sediment sorting is generally low, however locally increases due to fluvial activity (Srivastava et al, 2012). Contribution of the eolian processes is also probable as far as windblown material was detected within the supraglacial sediments near Schirmacher Oasis (Asthana and Chaturvedi, 1998).…”
Section: Study Areamentioning
confidence: 99%
“…grain sizes and texture). Recently, the use of more sophisticated multivariate statistical methods like factor analysis and discriminant functions have yielded more successful results in identifying the correct depositional process and environments and this is supported by the works of [21][22][23][30][31][32]. This study provides the first relatively detailed grainsize analysis of sandstones from part of the Ecca Group in the study area.…”
Section: Introductionmentioning
confidence: 73%
“…The bivariate plots are based on the assumption that statistical parameters reliably reflect differences in the fluid-flow mechanisms of sediment transportation and deposition [30]. Several researchers like [19,21,[30][31][32]64] have proven and documented that bivariate plots serve as reliable tools for identifying mechanisms of different environments of sedimentation. Furthermore, they reported that the bivariate plots are the most important and frequently used plots [4,63,65,66] These plots have also been attempted to differentiate between marine and fluvial sands.…”
Section: Bivariate Plots Of Statistical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The results were used to calculate grain size parameters following Folk and Ward (1957): mean grain diameter (M z ), standard deviation (sorting) (σ 1 ), skewness (Sk 1 ) and kurtosis (K G ) (peakedness of a particle size distribution curve). Kurtosis gives information about the The grain size distributions were interpreted according to Visher (1969) "...a sedimentological concept assuming that cumulative curves consist of several line segments, each segment symbolizing categories of particles (populations)" carried in different types of transport (Bartholdy et al 2007, Opreanu et al 2007, Mycielska-Dowgiałło & Ludwikowska-Kędzia 2011, Srivastava et al 2012. All grain size values are presented on the phi scale.…”
Section: Grain Size Analysismentioning
confidence: 99%